Prognosis of Covid-19 Patients with Raised Neutrophil- Lymphocyte Ratio (NLR) - Khalid, Maliha (International Journal of Pathology, 2022)
Introduction: Covid-19 disease is a deadly contagious disease leading to acute respiratory failure, septic shock and even death. Literature study showed that in severe Covid-19 patients, high NLR ratios suggested that there can be a hyper-inflammatory response to initial Covid-19 infection, accelerating to a severe hyper-cytokinaemia that could lead to an underlying endothelial dysfunction. Thus, systemic inflammation has been declared as a new predictor for Covid-19 patients’ outcomes.Objective: To demonstrate the importance of Neutrophil to Lymphocyte ratio (NLR) in the treatment of severe Pneumonia caused by SARS-CoV2 and its impact on the general prognosis.Methodology: Prospective analytical study, included 150 PCR positive patients admitted in Covid ITC, PAF Hospital from 1st February 2021 to 31st July 2021 including serving personnel and their dependents residing in the premises of PAF Air Base, Sargodha.Results: Out of 150 patients, 120 (80%) were discharged while 30 (20%) patients died out of which 5 died while being on HFNO therapy (High Flow Nasal Oxygen Therapy) and 25 patients were mechanically ventilated after consent. A comparison between NLR value of non-survival group to that of the survival group with the outcome of ITC patients via Chi square test revealed that there is a significant relationship (P value <0.005) between higher NLR values (equal to or more than 3) with increase in-hospital mortality.Conclusion: Our findings suggested that the NLR value appears to be a significant prognostic biomarker of multiple outcomes in critically ill Covid-19 patients.